O isolamento imposto pela pandemia para a pessoa idosa e a mediação de espaços virtuais: uma análise psicossocial - Vitória, Carla de Almeida (2021)
This research comprehends a psychosocial analysis about relational and affection dynamics, during the period of the pandemic social distancing, of elderly participants of a virtual space: The adopted method was the participatory research, which interacted and monitored the daily experiences of this group on the virtuality, besides individual interviews with six participants. The theoretical and methodological presuppositions are from the Historical-Sociological Psychology, based on Vigotski’s, Lane’s and Sawaia’s reflections about the subject’s complex objective/subjective totality in constant relation with the environment, and the conception of the dialectical exclusion/inclusion and the ethical-political suffering developed by the latter author. The comprehension about the affections, which is in the genesis of the subject’s constitution, occurs from Espinosa’s theory, rupturing the separative notion between reason/emotion, body/mind. It was also used in the theoretical referential, diverse contemporary literature about themes regarding the elderly. From these theoretical-epistemological basis, it is possible to comprehend that aging does not end the process of relations and activities of the individual in the world, it constitutes before, a moment of the ongoing life, imbued of affections, meanings and senses experimented in a singular way. The process of analysis aimed the living of the participants, occurring and active in the virtuality, as a path to the construction of the unities of sense which demonstrated: the group’s processuality, during the time of the research, elaborated in an affectional constellation generated in the context of the pandemical and political crisis in the country. It was verified among the elderly the living of enhancing affections created in the welcoming and friendships experiences in the group trough the good encounters, but also manifested potentiality of ailment as a reflection of the prejudice and depreciation of the elderly life lived in the pandemical scenario, generation ethical-political suffering. The Group as a living group and elderly recognition became a space that aids its participants in the facing of the social distancing, of the social and political pains, besides promoting communication among the elderly in and out of the virtual ambiance